Evaluation of The Facilities and Infrastructure in UPI Kindergarten Lab School based on The Principles of Child-Friendly School Design - Dinna Nafisa; Mokhamad Syaom Barliana; Fauzi Rahmannullah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2022)
This study aims to describe the criteria for the principles of child-friendly school design in the kindergarten environment, explain the condition of the facilities and infrastructure in the UPI Kindergarten Lab School, and the suitability of the facilities and infrastructure owned by the UPI Kindergarten Lab School with the principles of child-friendly school design. This uses a quantitative approach with a descriptive-evaluative method. Data collection techniques are in the form of observation and documentation. The research results related to the criteria for the principles of child-friendly school design in the kindergarten environment are known to have five aspects: security, health, comfort, safety, and convenience. The results of evaluating the suitability between the facilities and infrastructure of the UPI Kindergarten Lab School with the principles of child-friendly school design are 72.66% with good assessment criteria. The most superior and appropriate assessment is found in the assessment of health requirements and is less suitable for safety requirements.